2009
DOI: 10.1111/j.1365-2591.2009.01579.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of anterior teeth with dens invaginatus in the western mediterranean region of Turkey

Abstract: A careful oral examination, radiographs, a suitable treatment plan and follow-up programme are crucial for early diagnosis and treatment for teeth with dens invaginatus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
46
2
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 46 publications
(91 reference statements)
8
46
2
6
Order By: Relevance
“…This figure is considerably lower than the result of the study by Cakıcı et al[26] (0.8%) and by Kirzioğlu and Ceylan[27] (0.8%) among the Turkish population, and the result of the study by Ezoddini et al, (5.8%) among Iranian population, and the study by Poyton and Morgan. [28] These variations in prevalence between different populations may be due to ethnic variations, but may also be influenced by differences in criteria used for interpretation of dens invaginatus and also the specific teeth examined.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…This figure is considerably lower than the result of the study by Cakıcı et al[26] (0.8%) and by Kirzioğlu and Ceylan[27] (0.8%) among the Turkish population, and the result of the study by Ezoddini et al, (5.8%) among Iranian population, and the study by Poyton and Morgan. [28] These variations in prevalence between different populations may be due to ethnic variations, but may also be influenced by differences in criteria used for interpretation of dens invaginatus and also the specific teeth examined.…”
Section: Discussioncontrasting
confidence: 60%
“…Hamasha and Alomari[15] found a prevalence of 0.65% for individuals and 43.2% for all teeth in Jordanian dental patients. On the basis of person prevalence, the results of Cakici et al[26] and Kirzioğlu and Ceylan[27] were 1.3% and 12%, respectively, in Turkish dental patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it has been indicated that the bilateral dens invaginatus may be related with other dental anomalies such as microdontia, gemination, fusion, and taurodontism (13,14). In the present study, the symmetric dens invaginatus in the subjects was found to be 23.1%.…”
Section: Discussionsupporting
confidence: 51%
“…The incidence of dens invaginatus has been reported highest in maxillary lateral incisors with a Type I pattern. [12] Histological studies had shown intact dentine, presence of vital connective tissue or even fine canals with communication to the pulp in the invagination. [13] It has been suggested that the thin enamel at the invagination may break down and microorganisms may gain entry to the pulp by invading dentinal tubules.…”
Section: Discussionmentioning
confidence: 99%